Structure Characterization and Action Mechanism of an Antiaging New Compound from Gastrodia elata Blume. (6th May 2019) - Farooq, Umer; Pan, Yanjun; Lin, Yanfei; Wang, Ying; Osada, Hiroyuki; Xiang, Lan; Qi, Jianhua
Abstract : A new compound, bis(4-hydroxybenzyl)ether mono- β -L-galactopyranoside (1 ), was isolated from the rhizome of Gastrodia elata Blume. Its structure was elucidated using extensive spectroscopic analysis, including 1D and 2D NMR, HR-ESI-TOF-MS, and chemical derivatization. Compound1 extended the replicative lifespan of K6001 and the chronological lifespan of YOM36 yeast strains. To understand the mechanism of action, oxidative stress assessment, reactive oxygen species (ROS) and malondialdehyde (MDA) levels, catalase (CAT) and total glutathione peroxidase (GPx) activity assays, and replicative lifespan assay of sod1, sod2, uth1, and skn7 yeast mutant strains were performed. Results indicated the significant increase in the survival rate of yeast under oxidative stress after treatment with1 . ROS and MDA levels were reduced significantly. Meanwhile, the activity of CAT and GPx was significantly increased. The lifespan of sod1, sod2, uth1, and skn7 mutants of K6001 was not affected by1 . Furthermore, we investigated the gene expression related to longevity after administrating1 . The significant increase of Sir2 and reduction of Uth1 gene expression in the1 -treated group were observed. These results indicated that antioxidative stress played an important role in the antiaging effect of1 ; Sir2 and Uth1 genes were involved in antiaging effects of1 .